2001
DOI: 10.1016/s0928-8244(01)00232-2
|View full text |Cite
|
Sign up to set email alerts
|

New restriction fragment length polymorphism (RFLP) markers for Aspergillus fumigatus

Abstract: In this study, we isolated and tested restriction fragment length polymorphism (RFLP) markers for Aspergillus fumigatus based on PCR products amplified by the random amplified polymorphic DNA (RAPD) primer R108. Four DNA fragments, Afd, Af5, Af4, and Af4A, were amplified. Fragments Afd and Af5 were 85% and 88% identical at the DNA level to part of the Afut1 retrotransposon from A. fumigatus. Fragment Af4A is a duplication of fragment Af4 and both showed similarity at the amino acid level with endonucleases fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…Secondly, all PCR products derived from the various M. mycetomatis isolates presented the same restriction pattern after digestion by six different enzymes, which is in line with at least species homogeneity. That PCR-RFLP can be useful to detect fungal genetic variability has been shown repeatedly as well (5,14,17,24). To test whether the different primer combinations were species specific, they were tested on different fungal species.…”
Section: Discussionmentioning
confidence: 77%
“…Secondly, all PCR products derived from the various M. mycetomatis isolates presented the same restriction pattern after digestion by six different enzymes, which is in line with at least species homogeneity. That PCR-RFLP can be useful to detect fungal genetic variability has been shown repeatedly as well (5,14,17,24). To test whether the different primer combinations were species specific, they were tested on different fungal species.…”
Section: Discussionmentioning
confidence: 77%
“…To achieve finer discrimination of A. fumigatus strains, some authors have used different methods in combination (1,42,45). However, applying multiple tests makes the task of typing A. fumigatus more laborious, and some typing methods may be compromised in their accuracy, for example, because interpretation of band sizes is open to error.…”
Section: Discussionmentioning
confidence: 99%
“…One study even drew the conclusion of a neg-VOL. 45,2007 A. FUMIGATUS MLST 1475 on May 12, 2018 by guest http://jcm.asm.org/ ative association between clinical and environmental isolates (43). By contrast, two studies found indistinguishable isolates in several patients, a situation compatible with cross-infection with a common strain type (12,27); the finding is also more likely to arise in studies based on typing methods with low discriminatory power.…”
Section: Discussionmentioning
confidence: 99%
“…Other defective retrotransposons, including Afut2 [45], Af4 , Af4A [46], and Taf1 [47] could also be used successfully for strain typing in A. fumigatus. In the recent paper on sequencing of the A. fumigatus genome, several retrotransposons have been identified, about half of them belonging to the gypsy family of retrotransposons with long terminal repeats [48].…”
Section: Rflp Analysismentioning
confidence: 99%